Visualizing Malaysian Historical Figure Biography in Animation - Zulkifli, Mazni; Jamaludin, Nurul Nadiah (Semarak International Journal of Future Tourism and Hospitality Management, 2025)
The rise of digital media and entertainment had gradually become a part of the lifestyle among the Malaysian Gen Z. This abundance of digital contents was indeed enjoyable and giving them the availability for indefinite knowledge but most of them were deeply influenced by foreign influences. This subtle factor could bring a major significant to Malaysia’s Gen Z to be submerge with outside influence and gradually neglecting their own culture and losing their identity. This drives them away from understanding and appreciating the values of Malaysian culture especially regarding their own history and origins. Therefore, this study will use a qualitative method through contextual and literature analysis to study the method of re-introducing Malaysian historical figures to the new generation through animation media application in motion graphic style. Findings from this study is significant in enlightening Gen Z, thus preserving Malaysian heritage through online as a new digital content.